The Effect of Substitution of Seed Flour of Jackfruit (Artocarpus heterophyllus Lam.) on the Physicochemical and Organoleptic Characteristics of Macrons - Nurul Ummu Habibah; Nurjanna Albaar; Hamidin Rasulu (International Journal on Food, Agriculture and Natural Resources, 2021)
Jackfruit seeds are rich in carbohydrates, so they can be processed into food products such as macrons. Macron is a typical food of Ternate city which is usually made using wheat flour as the base ingredient. The purpose of this study was to determine the best ratio of substitution of jackfruit seed flour in macron manufacturing and to determine the physicochemical and organoleptic characteristics of macrons produced from different substitutions of jackfruit seed flour. This research investigated the substitution of jackfruit seed flour and wheat flour with formulation (P0 = 0%: 100%, P1 = 25%: 75%, P2 = 50%: 50%, P3 = 75%: 25% and P4 = 100. %: 0%), using a completely randomized design (CRD) consisting of five treatments with three replications to obtain 5 x 3 = 15 experimental units. The best treatment results showed the formulation of 25% jackfruit seed flour and 75% wheat flour (P1) in macrons with physical characteristics in the form of texture (fracture power) 12.25 N, color L * 56.42, a * 9.77, b * 25.44. The chemical properties are 18.313% protein, 11.846% fat, 63.693% carbohydrate, 0.916% ash, and 3.5% moisture. The organoleptic properties include aroma 4.12 (preference), taste 3.30 (neutral), color 4.14 (preference) and texture 4.05 (preference). Macron, with the addition of jackfruit seed flour, has a significant effect on physicochemical properties, including texture, color, moisture content, ash content, and protein, as well as organoleptic characteristics such as taste, aroma, color, and texture. Meanwhile, the addition of jackfruit seed flour to macrons has no effect on fat and carbohydrate levels.